ҚАРАҚАЛПАҚСТАНДАҒЫ ТҮРКМЕН ЭТНОНИМИ МЕНЕН БАЙЛАНЫСЛЫ ОЙКОНИМЛЕР - Қурбанов, М.Д. (FAN va JAMIYAT, 2025)
The article analyzes the ethnooikonyms of Karakalpakstan, including the Turkmen people, names associated with the names of its clans, the importance of their study, the history of migration of Turkmen to this region, and the areas of their settlement.